NEW DAWN FADES: FROM IMAGING TO QUANTITATIVE IMAGING BIOMARKERS AND BEYOND - Lučić, Miloš A. (Scripta Medica, 2019)
In the modern ages of rapid technological and computational advances, development of numerous novel diagnostic imaging techniques have enabled not only visual detection of disease processes, but also provided the tools to achieve quantified functional, structural, dynamic, metabolic, and molecular information. A pathway toward the quantitative imaging by use of quantitative imaging biomarkers analysis has been widely opened, enabling further development of radiomics, radiogenomics, and radioproteinomics analysis in addition, and initiating the dawn of theranostics, eventually bringing the wishful personalized medicine concept closer to reality.